10 Years Slewe. - Fuchs, Rudi H.; Slewe, Martita; Slewe Galerie, Amsterdam (Amsterdam : Slewe Galerie Amsterdam, 2004)
Jones, Zebedee ; Gijzen, Robbert-Jan ; Drissen, Paul ; Zeniuk, Jerry ; Aalders, Steven ; Wéry, Marthe ; Roeland, Jan ; Walsh, Dan ; Beekman, Merina ; Gerwers, Martin ; Shanahan, Sean ; Geurts, Joris ; Smits, Kees ; Jacklin, Michael ; Meller, Ingo ; van den Broeck, Frank ; Colton, Adam ; Davis, Peter ; de Koning, Krijn ; Klein, Martina ; Davenport, Ian ; Tuzina, Günter ; Bloemheuvel, Ruud ; Kwakernaak, Marnix ; Schorbach, Alice ; Austen, David ; Strik, Elly ; Innes, Callum ; Roberts, Perry ; Schleiffert, Charlotte
This publication appears at the occasion of the 10th anniversary of Slewe Gallery in Amsterdam, October 2004
Engels
Nederlands
boek